Masculinity norms, stress underestimation, psychological strain, and well-being in Japanese elite male athletes - Ojio, Y.; Izawa, S.; Watanabe, Y.; Oliffe, J. L.; Rice, S. M. (International Journal of Sport and Exercise Psychology, 2026)
Many elite male athletes experience mental health challenges yet remain reluctant to seek help. This reluctance is shaped not only by external stigma but also by internalised factors such as stress underestimation and conformity to restrictive masculinity norms, psychological strain, and subjective well-being among elite athletes. A cross-sectional survey was conducted with 227 male elite rugby players in Japan. Masculinity was assessed across five dimensions: high social status, physical and psychological toughness, high agency, low effeminacy, and superiority over women. Stress underestimation was measured across four domains: excessive self-efficacy for managing stress, insensitivity to stress, overgeneralisation of stress, and evasive attitudes toward stress. Multiple regression analyses revealed that stronger adherence to restrictive masculinity norms was associated with greater stress underestimation (B = 0.10, p < .001). Among masculinity dimensions, low effeminacy showed the strongest associations with overall stress underestimation (B = 0.36, p < 0.01) and evasive attitudes toward stress (B = 0.09, p = .03). Physical and psychological toughness was positively associated with psychological strain (B = 0.27, p = .02), while stress underestimation was negatively associated (B = -0.26, p = .01). Their interaction was marginal (B = -0.08, p = .07), indicating that toughness predicted higher strain when stress negation was low. Psychological strain was negatively associated with well-being (B = -0.41, p < .001). These findings suggest that rejecting femininity and emphasising toughness may mask psychological while sustaining short-term perceptions of well-being. Promoting emotional literacy and flexible masculine identities may support healthier adaptation in elite sport.